The patient experience of fatigue in motor neurone disease - Gibbons, Chris J. (Frontiers in Psychology, 2013)
Aims This paper is a qualitative investigation that aims to investigate the lived experience of fatigue in patients with motor neurone disease – a progressive and fatal neurological condition. Background Fatigue is a disabling symptom in motor neurone disease (MND) that affects a large number of patients. However, the term ‘fatigue’ is in itself imprecise, as it remains a phenomenon without a widely accepted medical definition. This study sought to investigate the phenomenon of fatigue from the perspective of the MND patient. Methods Ten patients with MND participated in semi-structured recorded interviews at a regional neuroscience centre in Liverpool, U.K. Transcripts analysis was broadly informed by the principles of interpretative phenomenological analysis (IPA). Findings Fatigue was unanimously explained to be disabling and progressive phenomenon. Participants described two forms of fatigue: whole-body tiredness, or use-dependent reversible muscle weakness related to exertion of limb and bulbar muscles. Both weakness and whole-body tiredness could be experienced simultaneously, and patients used the terms ‘fatigue’ and ‘tiredness’ interchangeably. Alongside descriptions of fatigue themes of Adaptation, Motivation, Avoidance, Frustration and Stress were revealed. Fatigue could be defined as “reversible motor weakness and whole-body tiredness that was predominantly brought on by muscular exertion and was partially relieved by rest”. Conclusion The results of this study support a multi-dimensional model of fatigue for patients with MND. Fatigue appears to be experienced and explained in two ways, both as an inability to sustain motor function and as a pervasive tiredness. Fatigue was only partially relieved by rest and tended to worsen throughout the day. It is crucial that MND care practitioners and researchers appreciate the semantic dichotomy within fatigue.